2013
DOI: 10.1002/mnfr.201300104
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat meal induced postprandial inflammation

Abstract: Raised levels of circulating inflammatory markers are associated with coronary artery disease, obesity and type II diabetes. It has been proposed that the ingestion of high-fat meals may serve as a stimulus to raise systemic inflammatory tone, although interventional studies have yielded conflicting results. We here review 57 studies of high-fat meal induced acute postprandial inflammation to identify the most frequently reported markers of postprandial inflammation and to compare these results with the highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
158
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 93 publications
11
158
3
2
Order By: Relevance
“…The present review found that the majority of studies detected an increase in IL-6 after the consumption of an HFM, which agrees with the findings of Herieka and Erridge (12). The increase is generally robust, because the average relative increase is ;100% of the baseline value; thus, IL-6 is quite FIGURE 3 Correlations of several study variables with percentage change in IL-6 from pre-to post-HFM in healthy participants.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The present review found that the majority of studies detected an increase in IL-6 after the consumption of an HFM, which agrees with the findings of Herieka and Erridge (12). The increase is generally robust, because the average relative increase is ;100% of the baseline value; thus, IL-6 is quite FIGURE 3 Correlations of several study variables with percentage change in IL-6 from pre-to post-HFM in healthy participants.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, TNF-a, like IL-6, is believed to increase quickly in the poststimulus period, peaking at ;2-3 h, then returning quickly to baseline (12). However, the findings of the current review disagree with this notion in the context of an HFM.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations